2000
DOI: 10.1074/jbc.275.2.1485
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Gene A18R DNA Helicase Is a Transcript Release Factor

Abstract: Prior phenotypic analysis of a vaccinia virus gene A18R mutant, Cts23, showed the synthesis of longer than wild type (Wt) length viral transcripts during the intermediate stage of infection, indicating that the A18R protein may act as a negative transcription elongation factor. The purpose of the work described here was to determine a biochemical activity for the A18R protein.Pulse-labeled transcription complexes established from intermediate virus promoters on bead-bound DNA templates were assayed for transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…The A18R polypeptide has classical DNA-dependent nucleic acid helicase motifs and DNA helicase activity specific for DNA:DNA hybrids less than 20 nt in length (Simpson & Condit, 1995). Extracts from infected cells depleted of A18R by growth of the mutant under non-permissive conditions did not support transcript release in an in vitro assay (Lackner & Condit, 2000). Interestingly, purified A18R was incapable of supporting transcript release unless extract from uninfected cells was also provided.…”
Section: Termination Of Intermediate and Late Transcriptionmentioning
confidence: 97%
“…The A18R polypeptide has classical DNA-dependent nucleic acid helicase motifs and DNA helicase activity specific for DNA:DNA hybrids less than 20 nt in length (Simpson & Condit, 1995). Extracts from infected cells depleted of A18R by growth of the mutant under non-permissive conditions did not support transcript release in an in vitro assay (Lackner & Condit, 2000). Interestingly, purified A18R was incapable of supporting transcript release unless extract from uninfected cells was also provided.…”
Section: Termination Of Intermediate and Late Transcriptionmentioning
confidence: 97%
“…The genes encoding these proteins all have early promoters, except for the three late transcription factors, which have intermediate promoters. The A18 protein, a putative helicase with a role in the release of RNA from transcription complexes (79,80), was detected, but the peptide abundance was below the threshold that we chose for significance. A transient association with the transcription complex, as well as other technical factors, could explain this result.…”
Section: Vaccinia Virus Replisome and Transcriptome Proteinsmentioning
confidence: 99%
“…Although any part of the duplicated region in RifR9 could be responsible for resistance to rifampin, we focused on A17 because previous studies had shown an interaction between D13 and the N terminus of A17 (5,14), whereas A18 is a DNA-dependent helicase involved in transcription (35,36) and A19 is involved in a late stage of morphogenesis (37,38). A17 is a 23-kDa protein that undergoes several modifications, including C-and N-terminal cleavages and phosphorylation.…”
Section: Isolation Of a Gene Duplication Mutant With Rifampin Resistamentioning
confidence: 99%